Identification of regulatory targets for the bacterial Nus factor complex - Gabriele Baniulyte (Nature Portfolio, 2017)
The Nus factor complex regulates rRNA folding and prevents Rho-dependent transcription termination in bacteria. Here, Baniulyte et al. show that it also inhibits translation of one of the Nus factor-encoding genes, suhB, and probably regulates the expression of other genes in diverse bacterial species.